1998
DOI: 10.1096/fasebj.12.1.101
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of TNF-α-induced ceramide generation and apoptosis in resistant human leukemia KG1a cells by the P-glycoprotein blocker PSC833

Abstract: Tumor necrosis factor (TNF-alpha) is a cytokine with antitumor activity against several cellular models. TNF-alpha-induced apoptosis seems to be mediated by a signaling pathway termed 'sphingomyelin-ceramide' pathway, which consists of the hydrolysis of sphingomyelin and the production of its breakdown product ceramide. Our study shows that KG1a cells, which are inherently resistant to TNF-alpha and do not produce ceramide upon cytokine stimulation, can be sensitized by the use of the P-glycoprotein inhibitor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(59 citation statements)
references
References 54 publications
1
58
0
Order By: Relevance
“…To con®rm our Western blot results that caspase-8 is not activated, we also performed Western blot analysis of the pro-apoptotic protein Bid in untreated and b 2 m-treated cells and found that all three cell lines contain full-length Bid, but were not able to detect degradation of the p15 form of truncated Bid (tBid) (Rastegar and Safa, unpublished results). Another line of evidence that caspases-3 and -8 are not involved in b 2 m-induced apoptosis in HL-60/VCR is that, as we have shown, these cells overexpress P-gp, and several reports showed that cells induced to overexpress P-gp either by drug selection or by gene transfer experiments are resistant to a variety of apoptotic stimuli including serum starvation, Fas ligand, tumor necrosis factor and UVirradiation (Robinson, et al, 1997;Bezombes, et al, 1998;Smyth, et al, 1998;Pallis and Russell, 2000) since caspases-3 and -8, but not caspase-9, activations are inhibited in P-gp expressing cells (Smyth et al, 1998;Ruepi et al, 2000). Interestingly, P-gp cannot inhibit caspaseindependent apoptosis (Ruepi et al, 2000).…”
Section: Discussionmentioning
confidence: 60%
“…To con®rm our Western blot results that caspase-8 is not activated, we also performed Western blot analysis of the pro-apoptotic protein Bid in untreated and b 2 m-treated cells and found that all three cell lines contain full-length Bid, but were not able to detect degradation of the p15 form of truncated Bid (tBid) (Rastegar and Safa, unpublished results). Another line of evidence that caspases-3 and -8 are not involved in b 2 m-induced apoptosis in HL-60/VCR is that, as we have shown, these cells overexpress P-gp, and several reports showed that cells induced to overexpress P-gp either by drug selection or by gene transfer experiments are resistant to a variety of apoptotic stimuli including serum starvation, Fas ligand, tumor necrosis factor and UVirradiation (Robinson, et al, 1997;Bezombes, et al, 1998;Smyth, et al, 1998;Pallis and Russell, 2000) since caspases-3 and -8, but not caspase-9, activations are inhibited in P-gp expressing cells (Smyth et al, 1998;Ruepi et al, 2000). Interestingly, P-gp cannot inhibit caspaseindependent apoptosis (Ruepi et al, 2000).…”
Section: Discussionmentioning
confidence: 60%
“…Also drug-selected cell lines have been shown to be less sensitive to apoptosis, but the cytotoxic compounds used to select resistant cells may induce other changes besides up-regulation of Mdr1 proteins. [39][40][41] In these studies PSC833 is often used as a Mdr1 inhibitor, but may itself increase apoptosis. 42 Regarding the mechanism involved, it has been observed that increased expression of MDR protein lowers the sensitivity of the cell to caspase-dependent apoptosis by decreasing the caspase-3 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, TNF-a activates a sphingomyelinase that induces apoptosis through the generation of ceramides from sphingomyelin (Kolesnick, 1992;Hannun, 1994;Kolesnick and Golde, 1994). P-gp-dependent sphingomyelin excretion may inhibit TNF-a-induced ceramide production and subsequent apoptosis (Bezombes et al, 1998).…”
Section: Introductionmentioning
confidence: 99%